2015
DOI: 10.1007/s00705-015-2710-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of antibody repertoires to the CD4 binding site of gp120 of a Chinese HIV-1-infected elite neutralizer, using 454 sequencing and single-cell sorting

Abstract: Broadly neutralizing antibodies (NAbs) against the CD4 binding site of HIV gp120 (CD4bs) have provided important information for vaccine design. In this study, we combined deep sequencing and single memory B cell sorting to isolate CD4bs-directed NAbs from a Chinese HIV-1-infected elite neutralizer. We first performed 454 pyrosequencing to capture the IGHV1, IGKV, and IGLV germline gene families. IGHV1-2*02, the heavy chain germline V gene (VH) of the CD4bs-directed bNAb VRC01, was found to have a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In support of our finding, a recent detailed analysis of CD4bs Abs suggested that the gene repertoire for recognition of the CD4bs region comprises of antibodies with different paratopes that can serve as determining factors for their neutralizing breadth and potency59. Similarly in another study60, it was shown that NAbs against the CD4bs region can develop by rearrangement from other variable heavy chain genes like VH5-51, rather than VH1-2 or VH1-46 gene. The 1F6 scFv, identified using BG505:SOSIP.664 as antigenic bait, also showed CD4bs specificity, with a VH1-46 heavy chain gene usage and is in consonance with observation that most of the CD4bs antibodies can be gene restricted.…”
Section: Discussionsupporting
confidence: 86%
“…In support of our finding, a recent detailed analysis of CD4bs Abs suggested that the gene repertoire for recognition of the CD4bs region comprises of antibodies with different paratopes that can serve as determining factors for their neutralizing breadth and potency59. Similarly in another study60, it was shown that NAbs against the CD4bs region can develop by rearrangement from other variable heavy chain genes like VH5-51, rather than VH1-2 or VH1-46 gene. The 1F6 scFv, identified using BG505:SOSIP.664 as antigenic bait, also showed CD4bs specificity, with a VH1-46 heavy chain gene usage and is in consonance with observation that most of the CD4bs antibodies can be gene restricted.…”
Section: Discussionsupporting
confidence: 86%
“…9 The CDR3 sequence of the V H and V L genes has been effectively determined by the MiSeq system; 10 a single-domain antibody gene was successfully determined by the MiSeq system using a 2 × 250 paired-end module; 11 and the entire V H gene was successfully sequenced using the 454 pyrosequencing system. 12 However, sequencing of the entire single-chain variable fragment (scFv) gene, which contains 750–800 bases, could not be achieved using any of these NGS platforms, to the extent of the authors' knowledge. In one study, to obtain the whole scFv gene sequence, HCDR3 sequences were first determined by the MiSeq system; the entire scFv gene was then generated by two-step linker PCR using primers based on the heavy chain complementarity-determining region 3 (HCDR3) sequences, and its sequence was determined by Sanger sequencing analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The expression vectors for SARS-CoV-2 RBD (GenBank No: MN908947) which carries the Avi-tag sequence for biotinylation at the 3’ end of the gene were constructed using the vector pDRVI1.0 ( 22 , 23 ). After expression and purification, the proteins were biotinylated by utilizing a biotin ligase Bir A500 kit (Avidity, USA) to conjugate with the streptavidin-fluorochrome reagents as previously described ( 24 ). Further, Streptavidin-phycoerythrin (SA-PE) (E4011, Sigma, USA) was mixed with biotinylated RBD as previously reported to do single B cell sorting ( 25 ).…”
Section: Methodsmentioning
confidence: 99%